Social and Solidarity Economy as a Driver of Sustainable Development andTerritorial Peace: Productive Alternatives in the District of Lerma, Cauca - Cabrera Muñoz, Dayra Ibeth; Meneses Cerón, Luis Ángel; Davalos Ortiz, Luis Felipe; Pechené Rodríguez, Marco Fidel (Cooperativismo & Desarrollo, 2025)
This study analyzes sustainable agricultural alternatives in the township of Lerma, Cauca, with the aim of identifying productive options that contribute to the substitution of illicit crops and the strengthening of legal local economies. A mixed methodology was used, combining qualitative techniques—such as interviews and document analysis—and quantitative techniques using regression analysis, considering sociodemographic variables such as gender, ethnicity, education, health insurance, and income. The results show that, although communities have made significant progress in the manual eradication of coca crops, structural barriers related to access to land, educational level, and participation in government programs persist. The research highlights the importance of designing differentiated policies that promote the inclusion of women and Afro-descendant communities, as well as the strengthening of local productive capacities. It concludes that the development of viable agricultural alternatives is essential to consolidate territorial peace processes and promote sustainable rural development in municipalities historically affected by illicit economies.